A contribution of the reliability based approach for cylindrical composite of sensitivity analytical design. Issue 3 (3rd July 2017) - Hocine, A.; Maizia, A.; Chérifi, M.; Chapelle, D.
Abstract: The present paper focuses on the sensitivity evaluation of analytical design tool of cylindrical composite structures to geometrical and mechanical uncertainties through a reliability approach based on the Monte Carlo method. The present tool design is developed to study the analytical mechanical response of multilayered cylindrical composite structures under pressure and to access strain and stress states. Using the hoop stress for each ply, the Monte Carlo method is used to predict the distribution function of the mechanical response, for random design variables of composite structure. Three random design variables with uncertainties are selected, namely: composite elastic constants, ply angles and finally the mechanical loading (pressure). To ensure accuracy of results, we performed 10 4 simulations. The results obtained show that the probability of failure increases significantly when all the random variables are considered simultaneously.